FORMULATION OF POLICIES TO STRENGTHEN AND OPTIMIZE THE ADIWIYATA PROGRAM TOWARDS ENVIRONMENTALLY FRIENDLY SCHOOLS - Nuri Kartini (Ann Publisher, 2024)
Program Adiwiyata School is an initiative of the Indonesian government to encourage schools to implement sustainability and environmental protection principles. This program aims to raise awareness among ecological students and develop environmental behavior. Adiwiyata schools generally have a good waste management system. Among them are separating organic and inorganic waste, composting, and reusing or recycling waste according to the 3R principle (reduce, reuse, recycle). Energy saving. The program aims to reduce school energy consumption by using energy-efficient lights, turning off unused electrical appliances, and raising awareness among students and staff, about energy saving. Adiwiyata School often prioritizes the use of natural resources, such as the use of rainwater to irrigate school gardens, maintain the presence of native vegetation, and reduce the use of harmful chemicals. One of the main goals of Adiwiyata School is to increase students' understanding of the environment and sustainable development. This is done through formal and informal educational activities such as learning on the school curriculum, extracurricular activities and field trips to places related to the environment. The results of the discussion can be concluded that The school as the target of the adiwiyata program is very enthusiastic to implement the adiwiyata school program in stages, it is hoped that there will be local government policies or agencies related to the adiwiyata school program and there will be rewards for district, provincial, national and independent adiwiyata schools, a strong commitment from all stakeholders is needed and good cooperation and synergy between related parties.